School Experience Program’s Role As the Field Experience Practice of Teacher Candidates - Deshinta Puspa Ayu Dwi Argaswari; Adesti Komalasari (Universitas Pahlawan Tuanku Tambusai, 2022)
The aim of this research is to explore the role of School Experience Program (SEP) as the field experience program for FOE teacher candidates. The study uses a qualitative method of research. Data is collected through the documentations of SEP documents, teacher candidates’ e-portfolio, and interview as addition. The research is conducted during the SEP on FALL 2020/2021. The results showed that the designed SEP is able to transform the Teacher candidates beliefs toward the teacher profession. Interestingly, each stage of SEP took different roles in shaping the Teacher candidates beliefs about teaching profession. Year 1 SEP has roles for Teacher candidates to understand the teaching and learning process, the learners, and also learn to think as a teacher. Year 2 SEP has a role for teacher candidates to learn to teach the subject matter knowledge including the administrations, teaching materials. preparation and evaluation. Year 3 of SEP has a role for teacher candidates to implement the theory of teaching and learning so they are able to develop the relevant materials. Year 4 SEP has a role for Teacher candidates to understand the teaching profession, and develop tools and disposition to study teaching